Efficacy and safety of filgotinib in patients with rheumatoid arthritis: week 156 interim results from a long-term extension study - Hendrik Schulze-Koops; Tsutomu Takeuchi; Daniel Aletaha; Maya H Buch; Yoshiya Tanaka; Ricardo Blanco; Paul Emery; Jacques-Eric Gottenberg; Bernard G Combe; Roberto Caporali; Patrick Verschueren; Vijay Rajendran; et al. (RMD Open)
Background Janus kinase inhibitors are an effective option for achieving sustained remission or low disease activity in patients with rheumatoid arthritis (RA) following inadequate response to conventional synthetic disease-modifying anti-rheumatic drugs. Filgotinib is a Janus kinase 1–preferential inhibitor available in two doses for moderate-to-severe RA. We report the long-term efficacy and safety of filgotinib.Methods In the ongoing long-term extension study FINCH 4 (NCT03025308), patients continue filgotinib 200 mg or 100 mg from FINCH 1, 2 or 3 or receive filgotinib 200 mg or 100 mg de novo. Efficacy assessments up to week 156 include American College of Rheumatology 20% response (ACR20), Disease Activity Score 28 using C-reactive protein of <2.6, Clinical Disease Activity Index of ≤2.8, Simplified Disease Activity Index of ≤3.3 and Boolean remission (1.0 and 2.0) with non-responder imputation.Results In patients with an inadequate response to methotrexate, 60.2% and 54.6% receiving de novo filgotinib 200 mg and 100 mg had an ACR20 at week 156, respectively, as did 67.3% and 59.5% of those who continued filgotinib 200 mg and 100 mg. At week 156, Boolean remission 1.0 was achieved by 18.8% and 15.4% of patients treated with de novo filgotinib 200 mg and 100 mg, respectively, and by 21.1% and 18.5% when Boolean 2.0 criteria were applied. Similar efficacy data were seen in patients from FINCH 2 and 3. Safety data were consistent with the known safety profile of filgotinib.Conclusion In FINCH 4, filgotinib 200 mg and 100 mg (continuous or de novo) demonstrated sustained efficacy up to week 156 in patients enrolled from FINCH 1, 2 or 3, with no unexpected safety results.